Distributive Justice: Lessons of a Pandemic - José Filipe Monteiro (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
For almost six months, the mass media are delivering round the clock news, reports, and chronicles about the Covid19 pandemics. Issues about medical problems focus on prevention, by confinement or discovery of a vaccine, but also around treatment by a drug, new or one already existing in the world pharmacopeia, to treat the damages the virus can cause in our bodies. During the first days and weeks of this pandemic, one of the topics of discussion centered on the shortage of ventilators in Intensive Care Units (ICU) all around the world. It focalized around the bioethical principle of distributive justice.